Fenomen „duszy” w heksaemeronie - Lasek, Paweł Adam (Verbum Vitae, 2022)
The work provides an analysis of the first description of the creation (Gen 1) from the perspective of various categories of created entities, as reflected in the triple use of the verb ברא. Each occurrence of this verb in this biblical text means creating something new and adding this new entity to an already existing world, which gives rise to a new category of created things. The first such category are inanimate things which receive existence and are made only of dead matter. The second category are living creatures which have a body made of the same matter, but who also receive the element of life. The third category is man, who has a body made of the same matter, with the same element of life, but also the third element which makes him similar to God, in fact, God’s image. That third element is not named in the text, but we may see here what we call a soul. So, having a soul distinguishes man from all other beings created by God: Only man has a soul. Animals do not have it, nor do plants, nor the sun and the moon, which were idolized by the ancients – none of these has a soul but instead belong to the realm of dead matter.